Transcranial Magnetic Stimulation for the Treatment of Pharmacoresistant Nondelusional Auditory Verbal Hallucinations in Dementia - Anna Marras; Stefano Pallanti (Case Reports in Psychiatry)
Auditory verbal hallucinations (AVHs) are known as a core symptom of schizophrenia, but also occur in a number of other conditions, not least in neurodegenerative disorders such as dementia. In the last decades, Transcranial Magnetic Stimulation (TMS) emerged as a valuable therapeutic approach towards several neurological and psychiatric diseases, including AVHs. Herein we report a case of a seventy-six-years-old woman with vascular-degenerative brain disease, complaining of threatening AVHs. The patient was treated with a high-frequency temporoparietal (T3P3) rTMS protocol for fifteen days. A considerable reduction of AVHs in frequency and content (no more threatening) was observed. Although further research is needed, this seems an encouraging result.